Fundamentals of Kinetics of Tomato Drying Process - Djuraev Khayrullo Fayzievich; Rasulov Shukhrat Khujakulovich; Adizova Madina Ruzievna (Genius Journals, 2022)
The article gives scientifically grounded recommendations on the preservation, processing of fruit and vegetable products. Also, there are scientifically sound proposals and recommendations on existing problems and solutions in the system. In recent years, in order to fully meet the needs of the population in food and other agricultural products, in particular, vegetable products, comprehensive measures are being taken in the vegetable sector. New innovative technologies for growing vegetable crops, including tomatoes, are being introduced. At present, more than 200,000 hectares of land in the country are planted with vegetables, of which 45.8% are tomatoes, with an average yield of 24 tons per hectare
Keywords: Physicochemical properties; storage and processing; dehydration; farms